(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
This project’s main goal was to determine which column cross sectional form can hold the highest weight under various loading circumstances. Concentric and eccentric loads with uniaxial bending were applied. The subsequent case employed 50mm and 75mm eccentricity to one of the axes. This project’s goal was to determine the greatest load-bearing cross sectional form of a thin column. 18 shaped columns were made for this purpose. Six square columns, six circular columns, and six hexagonal columns. All columns had the same cross section area, length,weight, and reinforcing %. The columns were then tested on a loading frame to see which form would withstand the highest weight under concentricand eccentric loading conditions.